Employment barriers for South African graduates - Ash, Matthew Frank (My University, 2018)
Networx for career development (CC) embarked on the implementation of a government-funded work readiness programme in 2017, which was run in conjunction with the Transport Education Training Authority (TETA) in South Africa. The project was very successful and achieved a 68% absorption rate for the unemployed graduates who took part in the programme. Broadly, for the purpose of this report, absorption means the percentage of graduates who obtained employment as a direct result of participating in the work readiness programme. Based on the success of the work readiness programme, the stakeholders of the programme wanted to ascertain ways in which they could improve the current programme, by identifying the possible barriers to employment that exist for some South African graduates. The question of ‘what are the perceived barriers for employment that exist for some graduates’ was investigated, because the stakeholders realised they were potentially treating the problem of graduate unemployment and wanted to first understand the causes of unemployment for some South African graduates. This report is, therefore, intended to identify and then recommend possible solutions to unemployment for some South African graduates. The recommendations from this consultancy report will be used to produce a framework for another study that will look to alleviate the main barriers to graduate unemployment in South Africa identified from this report. Recommendations will be made from any clearly identified trends that are established from the results of the survey that are supported by the literature, previous research and data that was analysed from the literature review. If any trends are identified that do not support any past research or literature, then possible suggestions will be recommended for potential further studies. The results of this report will show that the most significant perceived barrier for graduates achieving employment in South Africa is a lack of skills that employers are looking for. The report will recommend that further studies be undertaken to ascertain exactly which skills are required by employers. 2 The report will also show that from the gathered data, the two most effective measures for alleviating graduate unemployment are the creation of jobs outside of the major economic hubs in South Africa, and the establishment of a work readiness programme for all South African graduates. Recommendations will also be made with regards to further studies regarding a framework that should be put together to identify what a work readiness programme should look like in South Africa.
MBA
Keywords: College graduates -- Employment -- South Africa.